Analisis Kadar Air Biochar Dengan Bahan Baku Tandan Kosong Kelapa Sawit (TKKS) - Nisa, Ulfatun; Sasmita, Aryo; HS, Edward (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Biochar can increase soil C levels and can increase plant growth by supplying a number of nutrients to improve soil physical and biological properties. The raw material for making biochar is Empty Palm Bunches (EFB). EFB are rich in lignocellulose (cellulose, hemicellulose and lignin). Biochar was made using a pyrolysis device at 400oC for 2 hours and flowed with 100 ml/minute N2 gas. Biochar from EFB in this study has met the requirements for activated carbon based on SNI 06-3730-1995, with a water content of 1,45%. Keywords: Biochar, Empty Palm Bunches (EFB), water content